DAYA TERIMA DAN ANALISIS ZAT GIZI PADA PEMPEK SUBSTITUSI TEPUNG MOCAF - Cutyanti, Cici; Afriyana Siregar, Betty Yosephin Simanjuntak (JURNAL MEDIA KESEHATAN, 2018)
Mocaf flour is a flour made from cassava root (Manihot escluenta) which hasa lower ash content that is around 0.4 percent, has a higher starch content and mocaf alsohas a higher fiber content than wheat. Mocaf flour in this research as the basic ingredientof making pempek. Pempek is a snack food made from ground corn, tapioca, salt, andwater. This study aims to determine the acceptance (texture, color, flavour, taste) and toknow the nutrients of energy and macro nutrients in pempek mocaf. The materials used inmaking pempek are mocaf flour, tapioca flour, anchovy, palm oil, carrot, garlic, salt, andwater. Treatment in this research pempekis F1 flour mocaf 100%, F2 mocaf flour 75%and tapioca flour 25%, while F3 uses 50% mocaf flour and 50% tapioca flour. Themethod ofresearch is pempek in organoleptic test by 40 panelis then pempek mostpreferred analyzed nutrient energy and macro nutrient. The method of nutrient analysisused for the protein test using Kjeldahl, fat using hydrolysis-soxhlet, and carbohydratesusing Luff scrhool. From the results of one way anova pempek one of the most preferredis pempek with 50 mocaf F3 flour treatment and 50% tapioca flour. There is a markeddifference to texture and taste and there is no significant difference in color and flavour.While after the analysis obtained energy 173.61 calories, 5.27 grams of protein, 4.81grams of fat, and carbohydrates 27.31 grams. From this study it can be concluded that F3treatment contains energy, protein and fat higher than pempek which is often circulated,while carbohydrate is lower than pempek that often circulate. Suggestion for furtherinvestigators can examine more about micro nutrient found in pempek made from mocafflour.